Towards the Sustainability of English Language Teachers Professionalism via Professional Development Programs: Extrinsic and Intrinsic Satisfactions - Omar, Ruzana; Ab Rashid, Radzuwan; Yusoff, Sarah; Ismail, Hanita Hanim; Saed, Hadeel; Yassin, Baderaddin; Al-Smadi, Omar Ali (Frontiers in Psychology, 2022)
Understanding the satisfaction of teachers is essential in designing and improving professional development programs. This study attempts to investigate intrinsic and extrinsic aspects of satisfaction of Malaysian ESL Primary school teachers after following their first-degree program. Descriptive analysis was used to analyse the survey research data collected from 30 secondary school English language teachers in Kuala Terengganu, east coast of Malaysia. The findings revealed that personal gains did not contribute much to professional development (PD) activities in relation to the level of the teacher's extrinsic satisfaction after following their first-degree PD program. The study indicates that teachers differ from each other in terms of the source of their motivation for PD, whether intrinsic or extrinsic, and the type of development they aim for. This is hoped to show direction to the policymakers and organizers of the PD program in enhancing the program by taking into consideration of the teachers’ satisfaction, seniority, and professional background.